Anxiety disorders in patients with thyroid nodules vs. thyroid cancer: a retrospective cohort study - Kornelius, Edy; Lo, Shih-Chang; Huang, Chien-Ning; Wang, Yu-Hsun; Yang, Yi-Sun (Frontiers in Endocrinology, 2025)
BackgroundThyroid nodules, often discovered incidentally, typically require long-term monitoring and may contribute to psychological distress. Despite their prevalence, the psychological impact of thyroid nodules remains underexplored.MethodsThis retrospective cohort study used data from the TrinetX platform (2010–2023), encompassing 118 million patients. Patients diagnosed with thyroid nodules were matched to those with thyroid cancer using propensity score matching for age, sex, race, socioeconomic status and comorbidities. The primary outcome was anxiety disorder risk, with secondary outcomes including depression, mood disorder, and insomnia.ResultsAfter matching, 138,803 pairs were analyzed, with a mean age of 52 years, 70% female, and 66% White. Comorbidities were well-balanced. Patients with thyroid nodules had a significantly higher risk of developing anxiety disorder compared to those with thyroid cancer (HR 1.06; 95% CI: 1.03–1.08). Conversely, thyroid nodule patients had lower risks of depression (HR 0.93; 95% CI: 0.90–0.96), mood disorders (HR 0.95; 95% CI: 0.92–0.98), and insomnia (HR 0.93; 95% CI: 0.89–0.97). Psychotic disorders showed no significant difference (HR 1.03; 95% CI: 0.90–1.17).ConclusionsThis study identifies a significant association between thyroid nodules and increased anxiety risk, while risks for depression, mood disorders, and insomnia were lower compared to thyroid cancer patients. Furthermore, a sensitivity analysis compared thyroid nodule patients to the general population and revealed elevated anxiety risk in patients with nodules, reinforcing that this increased risk is not solely attributable to cancer-related factors. Further research is warranted to confirm these findings and explore mechanisms underlying the psychological impact of thyroid nodules.